Views of university’s top management leaders on university-community engagement - Md. Yunus, Aida Suraya; Azman, Norzaini; Abdul Rahman, Shukran (Atlantis Press, 2018)
University-community engagement (UCE) activities may be side-lined by academics due to the greater emphasis given to research, publication and teaching in promotion and yearly appraisal. Thus, communities close to a university may not receive any benefits from the existence of a university in their larger neighbourhood. UCE is described by Carnegie Foundation for Advancement of Teaching as the collaboration between higher education institutions (HEIs) and their larger communities (local, regional or state, national, and global) for the mutually beneficial exchange of knowledge and resources in a context of partnership and reciprocity. Involvement in UCE activities progresses from informing to consulting, involving, collaborating, and lastly, empowering the community. It may be in the form of service, outreach, partnership or curricular. Teichler (2017) uses the term socially responsible university to refer to the need for a university to be relevant to the society and that “university has to pay attention as well that it serves the generally agreed function of generating, preserving and disseminating knowledge appropriately”. This paper share views of top management leaders on the current state of UCE initiatives and what needs to be done to create more impactful activities.